International and domestic experience of intellectual property legal protection on the Internet and separate methods of police crimes detection in this area - V. A. Korshenko; M. V. Mordvyntsev; D. V. Pashniev (Bulletin of Kharkiv National University of Internal Affairs)
The history of the development of international legislation and the conclusion of international treaties regarding the protection of intellectual property, starting with the Berne Convention on the Protection of Literary and Artistic Works, was considered. The World Convention on Copyright, the Agreement on Trade Aspects of Intellectual Property Rights, and the Copyright Agreement of the World Intellectual Property Organization were analyzed. An attempt to sign an Anti-Counterfeiting Trade Agreement was tracked. The history of the adoption of laws on the protection of intellectual property in the USA “On Combating Online Piracy” (SOPA) and “On Prevention of Real Network Threats to Economic Creativity and Theft of Intellectual Property” (PIPA) was studied.